2008
DOI: 10.1108/13598540810850300
|View full text |Cite
|
Sign up to set email alerts
|

Benefits, barriers, and bridges to effective supply chain management

Abstract: Purpose – The purpose of this article is to provide academics and practitioners a quantitative and qualitative analysis of the benefits, barriers, and bridges to successful collaboration in strategic supply chains. Design/methodology/approach – A triangulation method consisting of a literature review, a cross‐functional mail survey, and 51 in‐depth case analyses was implemented. Senior managers from purchasing, manufacturing, and logistics were targeted in the mail survey. The break down by channel category in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
499
1
19

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 564 publications
(542 citation statements)
references
References 58 publications
23
499
1
19
Order By: Relevance
“…With regard to the benefits, the management literature contains a number of works that identify the potential benefits that can derive from the integrated management of the supply chain in SMEs, some of the most notable being Fawcett et al (2008), Meehan and Muir (2008), Chen et al (2004) and Leopoulos et al (2007). Table 1 shows the main potential benefits that were identified in these studies.…”
Section: Supply Chain Integration In Smes Benefits Strengths Threamentioning
confidence: 99%
“…With regard to the benefits, the management literature contains a number of works that identify the potential benefits that can derive from the integrated management of the supply chain in SMEs, some of the most notable being Fawcett et al (2008), Meehan and Muir (2008), Chen et al (2004) and Leopoulos et al (2007). Table 1 shows the main potential benefits that were identified in these studies.…”
Section: Supply Chain Integration In Smes Benefits Strengths Threamentioning
confidence: 99%
“…Além disso, as três funções podem ser consideradas como clientes e fornecedoras internas durante o processo de criação de valor ao cliente (PIERCY, 2007). Entretanto, em alguns trabalhos há menção de que muitas empresas falham ao se integrar com clientes e fornecedores devido à baixa integração interfuncional que obtém em seus próprios limites operacionais (BARRATT, 2004;FAWCETT;MAGNAN;McCARTER, 2008). Autores diversos (PAGELL, 2004;OLIVA;WATSON, 2011) destacam também que poucos estudos explicam de forma detalhada o alinhamento interfuncional no nível micro.…”
Section: Introductionunclassified
“…Fawcett et al (2008) found that managers recognize that technology, information and performance measurement are major barriers to successful supply chain collaboration. Supply chain management requires a systems perspective, since management activities are fragmented across organizational boundaries (Holmberg, 2000).…”
Section: Performance Management In Industrial Clustersmentioning
confidence: 99%